The strategies preventing particle transportation into the inlets of nuclear power plants: Mechanisms of physical oceanography - Li, Jintao; Xu, Mengdi; Lin, Jianwei; Jiang, Yuwu (Frontiers in Marine Science, 2023)
The formation of aquatic organism aggregations near the inlets of nuclear power plants (NPPs) has become an important global concern, as the aggregated organisms can block the cooling systems of NPPs, and, therefore, threaten their operational safety. In this study we focus on the trajectory of aquatic organisms, that is., how these organisms can be transported to the inlets of NPPs by physical ocean processes related to currents and waves. The Changjiang NPP, located on the west side of Hainan Island in China, is occasionally subject to serious gulfweed blocking events in spring. To study the physical mechanism, with the use of a three-dimensional numerical current–wave-coupled model, the current and wave conditions near the NPP were simulated. Based on the model, several particle-tracking simulations were run to evaluate the extent of the blocking that occurred in the inlet of the NPP’s cooling system with different forcings introduced. The results showed that the windage effect and the surface Stokes drift induced by waves were the main causes of blocking events in the Changjiang NPP, with the former transporting surface particles from upstream and the latter transporting surrounding particles onshore, into the NPP’s inlet. Further simulations revealed that bending of the inlet and changing the offshore mouth to downstream mouth could limit the blocking greatly, as particles were seldom transported into the mouth by cross-shore transport processes such as the Stokes drift. We suggest that such findings may provide a valuable reference for the development of strategies to prevent aquatic organism aggregation events in other NPPs.